(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Fabric Softness is one of main factors in guiding consumers’ purchasing decisions, and many instrumental testing techniques quantifying this attribute have been proposed to substitute for its sensory evaluation. However, the performance is poor. By establishing a biomechanical model equivalent to the manner in which human fingertips sense the mechanical resistance against lateral compression of fabric, this study theoretically discusses the mechanical sensitivity of human sensing organs and the perceptual sensitivity of human sensory system. The results show that the mechanical sensitivity depends on the ratio of the mechanical resistance against compression of fabric to that of fingerpad, and the perceptual sensitivity on both the mechanical sensitivity and the capacity of human tactile system. Furthermore, the scatter among individual tactile evaluation on softness is attributed to the limitation of human tactile system processing stimulus information, and the assigned magnitude principally obeys a certain probability distribution, not a single averaging value statistically. In this sense, the deformability of soft tissues leads to an intrinsic difference of tactile evaluation from instrumental testing, although fabric compression property is detected on the same mechanical principle. The present conclusions will correct our misunderstandings in the effect-cause relationship between sensory attributes and instrumental testing.